Intergenic spaces: a new frontier to improving plant health. Issue 4 (26th September 2021) - Tonnessen, Bradley W.; Bossa‐Castro, Ana M.; Martin, Federico; Leach, Jan E.
Summary: To more sustainably mitigate the impact of crop diseases on plant health and productivity, there is a need for broader spectrum, long‐lasting resistance traits. Defense response (DR) genes, located throughout the genome, participate in cellular and system‐wide defense mechanisms to stave off infection by diverse pathogens. This multigenic resistance avoids rapid evolution of a pathogen to overcome host resistance. DR genes reside within resistance‐associated quantitative trait loci (QTL), and alleles of DR genes in resistant varieties are more active during pathogen attack relative to susceptible haplotypes. Differential expression of DR genes results from polymorphisms in their regulatory regions, that includes cis ‐regulatory elements such as transcription factor binding sites as well as features that influence epigenetic structural changes to modulate chromatin accessibility during infection. Many of these elements are found in clusters, known as cis ‐regulatory modules (CRMs), which are distributed throughout the host genome. Regulatory regions involved in plant–pathogen interactions may also contain pathogen effector binding elements that regulate DR gene expression, and that, when mutated, result in a change in the plants' response. We posit that CRMs and the multiple regulatory elements that comprise them are potential targets for marker‐assisted breeding for broad‐spectrum, durable disease resistance.